UTILIZATION OF STEM CELL THERAPY AS A NEW APPROACH TO OVERCOME REPRODUCTIVE DISEASES IN WOMEN - Sumadi; Warda, Rizki Zeillatul (Stem Cell Research and Development Center, Universitas Airlangga, 2024)
The human body contains approximately 37.2 trillion cells, each specialized to perform specific functions within tissues and organs. Stem cells, particularly mesenchymal stem cells (MSCs), have emerged as a promising therapeutic option for various medical conditions due to their regenerative and differentiation capabilities. Female infertility, which significantly impacts quality of life, often results from reproductive disorders such as premature ovarian failure (POF), polycystic ovary syndrome (PCOS), endometriosis, Asherman syndrome, and preeclampsia. Conventional treatments like hormone therapy are limited by long-term risks, including heart disease and cancer, while assisted reproductive technologies are hindered by ethical, safety, and financial concerns. This review explores MSC-based therapies as innovative alternatives for addressing female reproductive disorders. MSCs demonstrate potential in regenerating ovarian cells, restoring hormonal balance, and repairing uterine tissue. For POF, MSC therapy replenishes ovarian cells, improves hormone levels, and restores function. In PCOS, MSCs reduce inflammation and fibrosis while enhancing ovarian function. Endometriosis management benefits from MSCs' ability to repair endometrial damage and improve uterine receptivity. MSCs also show efficacy in reducing fibrosis and increasing vascularization in Asherman syndrome and repairing placental damage in preeclampsia by mitigating oxidative stress and inflammation. This review synthesizes findings from recent studies to highlight MSCs' role in advancing gynecological medicine, presenting them as a safe, effective, and sustainable therapeutic approach for treating infertility and enhancing reproductive health.